2016
DOI: 10.1371/journal.pone.0167163
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus-Associated Abortion and Vertical Transmission following Acute Infection in Cattle under Natural Conditions

Abstract: Foot-and-mouth disease (FMD) is a highly contagious and economically important viral disease of cloven-hoofed animals, including domestic and wild host species. During recent FMD outbreaks in India, spontaneous abortions were reported amongst FMD-affected and asymptomatic cows. The current study was an opportunistic investigation of these naturally occurring bovine abortions to assess causality of abortion and vertical transmission of FMDV from infected cows to fetuses. For this purpose, fetal tissue samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The outbreaks described herein were previously shown to be associated with FMDV serotype O by multiplex PCR (Ranjan, Biswal, Subramaniam et al., ). Serotype O is the most common serotype of FMDV associated with outbreaks in India, accounting for 80% of the outbreaks nationally (Biswal et al., ) and nearly 50% of outbreaks in the neighbouring state of Uttar Pradesh (Verma, Pal, Singh, Udit, & Yadav, ).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The outbreaks described herein were previously shown to be associated with FMDV serotype O by multiplex PCR (Ranjan, Biswal, Subramaniam et al., ). Serotype O is the most common serotype of FMDV associated with outbreaks in India, accounting for 80% of the outbreaks nationally (Biswal et al., ) and nearly 50% of outbreaks in the neighbouring state of Uttar Pradesh (Verma, Pal, Singh, Udit, & Yadav, ).…”
Section: Methodsmentioning
confidence: 93%
“…Immediately subsequent to the outbreaks, FMDV lineage O/ME‐SA/Ind‐2001d was identified by sequence analysis from multiple clinical samples from both farms. Further genomic, antigenic and clinical characterizations of the FMDV isolates from the farms included in this study have been reported in separate publications (Ranjan, Biswal, Subramaniam et al., ; Subramaniam et al., ).…”
Section: Methodsmentioning
confidence: 93%
“…The pastoral community members’ concern about foot and mouth disease as a cause of abortion in their cattle is similar to the findings of a study by Kothalawala et al [ 27 ] in Sri Lanka where farmers identified this disease as a cause of abortion in their cattle, but they had no adequate information regarding brucellosis as a cause of abortion in animals. Evidence also shows that foot and mouth disease causes abortion in cattle [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional cases were recorded for 39 days until the last new case of FMD on the farm was reported on 31 January 2014. Genomic analyses of viral isolates collected during the outbreak indicated that the causative strain categorized within O/ME‐SA/Ind‐2001d lineage (Ranjan et al., ). The vaccine strain used at this time in India belonged to O/IND/R2/75 lineage (Subramaniam et al., ), and recent studies have suggested that this vaccine strain provides adequate protection against infection caused by strains belonging to O/ME‐SA/Ind‐2001d lineage (Subramaniam et al., ).…”
Section: Methodsmentioning
confidence: 99%